Pengaruh Tayangan Vlog Ekspedisi “Langit Kelabu” Terhadap Sikap Gen Z Akan Hal Mistis - Erlangga Fajri Ramadanny; Eugenius Kau Suni (STIKes Ibnu Sina Ajibarang, 2024)
The concept of the mystical in society embodies an air of mystery, fear, suspense, horror, and the like, leading the inability of society to understand mystical phenomena to drive a high level of curiosity about such occurrences. Even the mystical has become a form of entertainment for society, one of which is through consuming horror content on YouTube. In the present era, Generation Z is a cohort whose lives have evolved with distinct thought patterns compared to preceding generations, parallel to the relentless development of the digital technology world. One manifestation of internet content or YouTube content is the